Gender in Science and Technology Interdisciplinary Approaches - Ernst, Waltraud; Horwath, Ilona (Gender Studies, 2013)
What role does gender play in scientific research and the development of technologies? This book provides methodological expertise, research experiences and empirical findings in the dynamic field of Science and Technology Studies. The authors, coming from computer science, social sciences, or cultural studies of science, discuss how to ask questions about gender and give examples for the application in interdisciplinary research, development and teaching. Topics range from the design of information and communication technologies, epistemologies of biology and chemistry to teaching mathematics and professional processes in engineering. Contributions by Anne Balsamo, Wendy Faulkner, Rebecca Jordan-Young, Barbara Orland, Els Rommes, and others.